Terapi Murottal Meningkatkan Hormon Î’ -Endorfin dan Menurunkan Tekanan Darah Lansia - Elis Hartati; Artika Nurrahima; Nurullya Rachma; Megah Andriany (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effect of murottal therapy on Î²-endorphin levels and blood pressure in older people. The method used is quasi-experimental with one group pre-test and post-test design. The results showed that the Î²-endorphin levels in older people before the intervention had a mean value of + 349,910 pg/ml, and after the intervention, the average value was + 432,849 pg/ml (p-value = 0.001). The study's systolic and diastolic blood pressure results before and after the intervention had a p-value = 0.000. In conclusion, Murottal therapy effectively increases levels of the hormone Î²-endorphin and lowers blood pressure. Keywords: Elderly, blood pressure, murottal therapy, Î²-endorphins